(untitled) (Hematology Meeting Reports, 2009)
The relationship between immunodeficiency and the increased frequency of non-Hodgkin lymphoma (NHL) was firstly noted nearly 35 years ago among transplanted patient, but it became more evident with the emergence of the human immunodeficiency virus (HIV) epidemic in the early 80’s.1 Since then, several epidemiological studies have assessed that HIV-infected individuals have 10 to 100-fold increased risks particularly for three types of NHL [i.e., primary central nervous system lymphoma (PCNSL); immunoblastic lymphoma and Burkitt’s lymphoma (BL)]. The clinico-pathological spectrum of AIDS-related NHLs includes: 1) BL and BL like lymphomas; 2) diffuse large B cell lymphoma (DLBCL) with immunoblastic features; 3) primary central nervous system lymphoma (PCNSL); and 4) two novel and rare entities, primary effusion lymphoma (PEL) and plasmablastic lymphoma of the oral cavity. Hodgkin’s disease (HD), is also seen with a higher frequency in HIV-infected persons,2 but it is not included among AIDS–defining conditions.